Advanced Electrocatalysts for Low-Temperature Fuel Cells - Rodríguez-Varela, Francisco Javier; Napporn, Teko W.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book introduces the reader to the state of the art in nanostructured anode and cathode electrocatalysts for low-temperature acid and alkaline fuel cells. It explores the electrocatalysis of anode (oxidation of organic molecules) and cathode (oxygen reduction) reactions. It also offers insights into metal-carbon interactions, correlating them with the catalytic activity of the electrochemical reactions. The book explores the electrocatalytic behaviour of materials based on noble metals and their alloys, as well as metal-metal oxides and metal-free nanostructures. It also discusses the surface and structural modification of carbon supports to enhance the catalytic activity of electrocatalysts for fuel-cell reactions.
Chapter 1. Introduction. Low-Temperature Fuel cells -- Chapter 2. Recent advances on electrocatalysts for PEM and AEM Fuel Cells -- Chapter 3. Electro-catalysis of alternative liquid fuels for PEM Direct Oxidation Fuel Cells -- Chapter 4. Overview of Direct Liquid Oxidation Fuel Cells and its Application as Micro-Fuel Cells -- Chapter 5. Application of novel carbonaceous materials as support for Fuel Cell electrocatalysts -- Chapter 6. Progress on the functionalization of carbon nanostructures for fuel cell electrocatalysts -- Chapter 7. Non-noble metal electrocatalysts for the Oxygen Reduction Reaction in fuel cells.
Keywords: Electrochemistry; Materials; Catalysis; Force and energy; Renewable energy sources; Electrochemistry; Materials for Energy and Catalysis; Renewable Energy; Catalysis